Excavations at Chester, the northern and eastern Roman extramural settlements : excavations 1990-2019 and other investigations - Dodd, Leigh (Archaeopress Roman archaeology, 2020)
This publication presents the results of fifteen archaeological investigations carried out within the Canabae to the north and east of the Roman legionary fortress at Chester between 1990 and 2019.